Occurrence of ochratoxin A and citrinin in Czech cereals and comparison of two HPLC methods for ochratoxin A detection - Polisenska, I; Pfohl-Leszkowicz, A; Hadjeba, K; Dohnal, V; Jirsa, O; Denesova, O; Jezkova, A; Macharackova, P (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2010)
The aims of the study were to obtain information about the occurrence of ochratoxin A (OTA) and citrinin (CIT) in cereals harvested in the Czech Republic and to compare two analytical procedures for detecting OTA. A total of 34 cereal samples, including two matrix reference materials (R-Biopharm, Germany), were analysed. The results were compared with the limit for raw cereal grains used as a foodstuff according to Commission Regulation No. 1881/2006, which allows a maximum OTA level of 5 µg kg(-1). Compared were two methods based on the high-performance liquid chromatography principle, one using the immunoaffinity columns OchraTest (VICAM) and the second based on solvent partition (PART), both followed by fluorescence detection. The highest OTA contents were found in two barley samples. According to the method employed, the results for the first sample (malting barley) were VICAM = 31.43 µg kg(-1) and PART = 44.74 µg kg(-1). For the second sample (feeding barley) they were VICAM = 48.63 µg kg(-1) and PART = 34.40 µg kg(-1). Two samples of bread wheat had an OTA content approaching the legal limit (VICAM = 4.71 µg kg(-1) and PART = 6.03 µg kg(-1); VICAM = 4.12 µg kg(-1) and PART = 3.95 µg kg(-1)). CIT was analysed using the PART method only, and its highest content (93.64 µg kg(-1)) was found for the malting barley sample with high OTA content (44.74 µg kg(-1) as analysed using PART).
Keywords: Citrinin; Food Inspection; Reproducibility of Results; kontrola potravin; reprodukovatelnost výsledků; voda; Česká republika; Limit of Detection; limita detekce; Chromatography, High Pressure Liquid; Seeds; Water; metody pro přípravu analytických vzorků; Hordeum; Czech Republic; vysokoúčinná kapalinová chromatografie; kontaminace potravin; ječmen (rod); semena rostlinná; citrinin; Analytic Sample Preparation Methods; Food Contamination; Edible Grain; ochratoxiny; jedlá semena; Ochratoxins